System medialny Irlandii - Menkes, Marcin (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
There are few countries where the relation between the shaping of democratic society and the development of the media is as perceptible as in Ireland. From the point of view of this paper, the breakthrough came when the media were granted statutory guarantes of freedom of expression and freedom of the media provided by the currently binding Constitution of 1937. Irish media law is going through a period of significant changes that have long been postponed. Some of these changes have only just taken place and it is too early to assess their impact, as is the case with the Defamation Act passed in 2009. There are still others issues waiting to be solved. There are simultaneous and significant processes, such as the digitalization of European television and considerable transformations in Irish society, which stimulate the discussion of changes. A comprhensive assessment of the system should probably be postponed till the end of the reforms, which are stifar from completion.